Sinodalitas Gereja dan Misi Tarekat MSC - Timotius Ata Leuehaq (Kelompok Studi Mitra Skolastikat MSC PinelengINELENG, 2022)
This paper reflects the question concerning how MSC Congregation think of its mission in the midst of the contemporary era as signified by the massively development of technology in the one hand, and the synodal church as Catholic church has declared in the other hand. I claim that, as an integral part of Catholic church, the congregation reflects on its identity and missionary involvement based on its specific spirituality. In relation to that, at least, there are two matters the congregation could think. First, the congregation need to remain listening to its own sources which are the foundations of its existence as a congregation, like: charism and the founder’s spirituality, statute and constitution, the chapters ‘documents, etc newly. It is needed so that the congregation is able to get the spirit and power to re-vivify and articulate newly the commitments for the renewal of identity and mission. Second, the congregation needs to listen to all who have good will outside of the congregation seriously, creatively and sincerely. It is needed for the congregation to be the integral part of the contemporary situation of the society. Just by that way, the congregation participates concretely and effectively in the spirit of establishing the synodality of the church as it has been on.